1992
DOI: 10.1002/bjs.1800790819
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer in Nigerian women

Abstract: A combined retrospective (1971-1980) and prospective (1981-1990) study of the epidemiology, clinical characteristics and pathology of breast cancer in a black African population was carried out. There were 1946 biopsy-proven cases, with a rate frequency of 33.6 per 100,000 patients per year. The age range was 14-96 years but 70 per cent of patients were between 26 and 50 years old. The cumulative frequency of cancer was 0.8 per cent at age < 20 years and 3.3 per cent at age < 25 years; the peak age range for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
68
3

Year Published

1995
1995
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 13 publications
6
68
3
Order By: Relevance
“…This figure is higher than what was reported more than a decade ago when 77% among breast cancer patients in Lagos presented in late stages [9]. Reports from other centres in Nigeria over the years showed that majority, ranging from 64% to 95% presented with late stages of the disease [2,3,10,13]. Fourteen percent had bilateral breast involvement at presentation in this study.…”
Section: Pathologycontrasting
confidence: 62%
See 3 more Smart Citations
“…This figure is higher than what was reported more than a decade ago when 77% among breast cancer patients in Lagos presented in late stages [9]. Reports from other centres in Nigeria over the years showed that majority, ranging from 64% to 95% presented with late stages of the disease [2,3,10,13]. Fourteen percent had bilateral breast involvement at presentation in this study.…”
Section: Pathologycontrasting
confidence: 62%
“…Fourteen percent had bilateral breast involvement at presentation in this study. Involvement of both breasts at presentation ranged from 1% to 9% in previous studies among breast cancer patients in Nigeria [3,9,10,13].…”
Section: Pathologymentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, carcinoma of the breast ranks first among malignant tumors affecting females in many parts of the world, including Saudi Arabia. 1 Wide variations in the spectrum of breast diseases and the epidemiology of mammary carcinoma in various countries [2][3][4][5][6][7][8][9] or ethnic groups [10][11][12] have been reported. In the Arab world, most of the studies on pathological conditions of the breast are related to its malignancies.…”
mentioning
confidence: 99%